COLLABORATIVE LEARNING AS A TOOL FOR CRITICAL THINKING AND ENGAGEMENT (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Collaborative learning (CL) is increasingly recognized as a transformative pedagogical strategy in higher education, aimed at enhancing critical thinking, student engagement, and collaborative competencies. This study investigates the role of structured collaborative learning activities—including group discussions, problem-solving tasks, and case studies—in promoting higher-order cognitive skills and active participation among undergraduate students. A mixed-methods design was employed, collecting quantitative data through surveys and pre/post critical thinking assessments, alongside qualitative insights from classroom observations and focus group interviews. Findings reveal that participation in collaborative learning significantly improves students’ analytical reasoning, problem-solving abilities, and engagement levels. Moreover, CL facilitates the development of interpersonal skills, communication, teamwork, and reflective thinking, fostering an inclusive and participatory learning environment. The study underscores the importance of integrating collaborative learning strategies into higher education curricula as a means of enhancing both academic performance and socio-emotional competencies essential for professional success. These results have practical implications for instructors, curriculum designers, and policymakers seeking to optimize student-centered learning environments.